Hebbian LTP in feed-forward inhibitory interneurons and the temporal fidelity of input discrimination. - Lamsa, K; Heeroma, J; Kullmann, D (2005)
Cortical information processing requires a delicate balance of excitatory and inhibitory signaling. How is this balance preserved during hippocampal memory encoding, which involves NMDA receptor-dependent long term potentiation (LTP)? This form of LTP occurs at synapses between pyramidal neurons but has not been detected in feed-forward inhibitory interneurons. We show that paired pre- and postsynaptic activity evokes pathway-specific LTP in half of rat stratum radiatum interneurons if cytoplasmic integrity is preserved. LTP occurs in aspiny feed-forward interneurons and propagates to pyramidal neurons as an enhancement of disynaptic inhibition. We also show that when LTP is restricted to synapses on pyramidal neurons, the temporal fidelity of synaptic integration and action potential generation in pyramidal cells is compromised. However, when LTP also occurs at synapses on feed-forward interneurons, temporal fidelity is preserved. We propose that Hebbian LTP at synapses driving disynaptic inhibition is necessary to maintain information processing without degradation during memory encoding.